Penyuluhan Bahaya Narkoba pada Siswa Madrasah Aliyah Negeri 1 Solok - Oktavia, Yosi; Mairen, Nadya Dwi Dara (PT Hakhara Akademia Indonesia, 2023)
Drug abuse among teenagers is a serious problem that can damage the future of the younger generation. This article reviews community service activities in the form of counseling on the dangers of drugs carried out at MAN 1 Solok. The purpose of this activity is to increase students' knowledge and awareness of the dangers of drugs and their impacts on health and social life. The methods used are interactive lectures, group discussions, and distribution of educational materials. The evaluation results showed a significant increase in students' knowledge and attitudes towards drugs after participating in the counseling. This activity is expected to be a model in efforts to prevent drug abuse among students.